Analisis Segmentasi Pasar Terhadap Volume Penjualan Melalui Keputusan Pembelian: (Survei Pada Toko Youth Sneakers) - Silvia Oktapiani Hayati (CV. ULIL ALBAB CORP, 2022)
This study aims to determine the analysis of market segmentation on sales volume through purchasing decisions (Survey of Youth Sneakers Shop Consumers). The method used is a quantitative approach with the survey method. With a research sample of 100 Consumers of Youth Sneakers Stores. The data used is primary data. The analytical tool used in this research is path analysis using SPSS 26.0. The results showed that the market segmentation perceived by the Youth Sneakers shop consumers had very good criteria. The Purchase Decision of the Youth Sneakers Store has very good assessment criteria and the Sales Volume at the Youth Sneakers Store has good criteria. Market segmentation and purchasing decisions have a significant influence on sales volume in Youth Sneakers shop consumers. Market Segmentation has a significant effect on Sales Volume at Youth Sneakers Store Consumers. Purchase Decisions have a significant effect on Sales Volume at Youth Sneaker Store Consumers. There is a mediating effect of purchasing decisions in mediating the relationship between market segmentation and sales volume in Youth Sneakers shop consumers.